Early Changes in Tumor Perfusion from T1-Weighted Dynamic Contrast-Enhanced MRI following Neural Stem Cell-Mediated Therapy of Recurrent High-Grade Glioma Correlate with Overall Survival. (14th March 2018) - Sahoo, Prativa; Frankel, Paul; Ressler, Julie; Gutova, Margarita; Annala, Alexander J.; Badie, Behnam; Portnow, Jana; Aboody, Karen S.; D'Apuzzo, Massimo; Rockne, Russell C.
Abstract : Background . The aim of this study was to correlate T1-weighted dynamic contrast-enhanced MRI- (DCE-MRI-) derived perfusion parameters with overall survival of recurrent high-grade glioma patients who received neural stem cell- (NSC-) mediated enzyme/prodrug gene therapy. Methods . A total of 12 patients were included in this retrospective study. All patients were enrolled in a first-in-human study (NCT01172964) of NSC-mediated therapy for recurrent high-grade glioma. DCE-MRI data from all patients were collected and analyzed at three time points: MRI#1—day 1 postsurgery/treatment, MRI#2— day 7 ± 3 posttreatment, and MRI#3—one-month follow-up. Plasma volume (V p ), permeability (K t r ), and leakage (λ t r ) perfusion parameters were calculated by fitting a pharmacokinetic model to the DCE-MRI data. The contrast-enhancing (CE) volume was measured from the last dynamic phase acquired in the DCE sequence. Perfusion parameters and CE at each MRI time point were recorded along with their relative change between MRI#2 and MRI#3 (Δ32 ). Cox regression was used to analyze patient survival. Results . At MRI#1 and at MRI#3, none of the parameters showed a significant correlation with overall survival (OS). However, at MRI#2, CE andλ t r were significantly associated with OS (p < 0.05 ). The relativeλ t r andV p from timepoint 2 to timepoint 3 (Δ32 λ t r and Δ32 V p ) were each associated with a higher hazard ratio (p < 0.05 ). All parameters were highly correlated, resulting in a multivariate model for OS including only CE at MRI#2 and Δ32 V p, with anR 2 of 0.89. Conclusion . The change in perfusion parameter values from 1 week to 1 month following NSC-mediated therapy combined with contrast-enhancing volume may be a useful biomarker to predict overall survival in patients with recurrent high-grade glioma.